PENGARUH PAPARAN KOMBINASI KORTIKOSTEROID BUDESONIDE & FORMOTEROL TERHADAP PERUBAHAN KEKASARAN RESIN KOMPOSIT TIPE BULK-FILL - Anugrah Amsal Pratama Biring; Isyana Erlita; R. Harry Dharmawan Setyawadhana (Universitas Lambung Mangkurat, 2021)
ABSTRACTBackground: Inhalation of asthma medication in the form of combination of the corticosteroid budesonide & formoterol which is acidic can affect the surface roughness of restoration materials such as composite resin. This is due to the significant change in the pH of saliva to 5.5 after 30 minutes of using an inhaler which can cause degradation of the polymer matrix composite resin and cause changes in surface roughness. Purpose: To determine the effect of exposure to the corticosteroid combination budesonide and formoterol on the roughness change of bulk-fill type composite resin. Methods: This study was true experimental research (pretest and post-test group design). The treatment group of bulk-fill type composite resin with exposure to a combination of budesonide & formoterol 160 / 4.5μg 2x1 inhalation; exposure to a combination of budesonide & formoterol 160 / 4.5μg 2x2 inhalation; without exposure to the combination budesonide & formoterol. The groups were tested using the Surface Roughness Tester. Results: One Way Anova and Post Hoc Bonferroni tests showed that there were significant differences between treatment groups (p<0.05).Conclusion: Exposure to a combination of budesonide and formoterol at a dose of 160 / 4.5μg 2x1inhalation and 2x2inhalation increased the roughness of bulk-fill type composite resin. Keywords: Bulk-fill type composite resin, combination of budesonide and formoterol, surface roughness. ABSTRAKLatar Belakang: Inhalasi obat asma yang berupa kombinasi kortikosteroid budesonide & formoterol yang bersifat asam dapat berpengaruh terhadap kekasaran permukaan bahan restorasi seperti resin komposit. Hal ini disebabkan terjadi perubahan yang signifikan pada pH saliva hingga berada di angka 5,5 setelah 30 menit menggunakan inhaler yang dapat menyebabkan terjadinya degradasi jaringan polimer matriks resin komposit dan menyebabkan perubahan kekasaran permukaan. Tujuan: Mengetahui pengaruh paparan kombinasi kortikosteroid budesonide dan formoterol terhadap perubahan kekasaran resin komposit tipe bulk-fill. Metode: Penelitian menggunakan metode eksperimental murni (pretest and post-test group design). Kelompok perlakuan resin komposit tipe bulk-fill dengan paparan kombinasi budesonide & formoterol 160/4,5μg 2x1 inhalasi; paparan kombinasi budesonide & formoterol 160/4,5μg 2x2 inhalasi; tanpa paparan kombinasi budesonide & formoterol. Ketiga kelompok diuji dengan alat Surface Roughness Tester. Hasil penelitian: Uji One Way Anova dan Post Hoc Bonferroni menunjukkan terdapat perbedaan yang bermakna antar kelompok perlakuan (p<0,05). Kesimpulan: Paparan kombinasi budesonide dan formoterol dosis 160/4,5μg 2x1 inhalasi dan 2x2 inhalasi meningkatkan kekasaran resin komposit tipe bulk-fill. Kata kunci: Kombinasi budesonide dan formoterol, kekasaran permukaan, Resin komposit bulk fill.